Dari Khong Kauw Hwee Ke MAKIN Boen Bio: Perjuangan Etnis Tionghoa di Surabaya Mempertahankan Eksistensi Agama Khonghucu Awal Abad XX sampai Awal Abad XXI - Rahayu, Shinta Devi Ika Santhi (Perkumpulan Program Studi Sejarah Se-Indonesia, 2024)
This study seeks to find answers to how Khong Kauw Hwee, who later changed his name to MAKIN Boen Bio, fought for the existence of the Confucian Religion. This study uses historical research methods. Source searches were carried out at the Boen Bio Library, the Medayu Agung Library in Surabaya, and the National Library of the Republic of Indonesia. Actualizing religious values through social and cultural activities is a strategic step to achieve support. An open attitude, prioritizing universal values and seriousness in supporting the achievement of integration is carried out not only for the benefit of Confucian religious communities but also to protect the position of ethnic Chinese in a pluralistic society. So in every social and cultural activity, Confucian religious communities under the MAKIN Boen Bio institution do not leave behind other elements of society, including non-Confucian and non-Chinese institutions.